An introduction to classical molecular dynamics simulation for experimental scattering users. Issue 3 (7th May 2019) - McCluskey, Andrew R.; Grant, James; Symington, Adam R.; Snow, Tim; Doutch, James; Morgan, Benjamin J.; Parker, Stephen C.; Edler, Karen J.
Abstract : This work introduces an interactive open educational resource aimed at introducing users of elastic scattering techniques to classical molecular dynamics simulation and showing how the simulation may be used to inform the experimental analysis. Abstract : Classical molecular dynamics simulations are a common component of multi‐modal analyses of scattering measurements, such as small‐angle scattering and diffraction. Users of these experimental techniques often have no formal training in the theory and practice of molecular dynamics simulation, leading to the possibility of these simulations being treated as a `black box' analysis technique. This article describes an open educational resource (OER) designed to introduce classical molecular dynamics to users of scattering methods. This resource is available as a series of interactive web pages, which can be easily accessed by students, and as an open‐source software repository, which can be freely copied, modified and redistributed by educators. The topics covered in this OER include classical atomistic modelling, parameterizing interatomic potentials, molecular dynamics simulations, typical sources of error and some of the approaches to using simulations in the analysis of scattering data.